Taking Sides : clashing views on controversial issues in abnormal psychology - Halgin, Richard P. (Connecticut : McGraw Hill Education, 2003)
There are many complex issues that arise in the field of abnormal psychology ; in this book you will read about 20 controversial matters with which mental health expert struggle.